Analisis Efektivitas Pelaksanaan Pelatihan Dan Pengembangan Karyawan Di Lingkungan PT IMST - Adela Aurelia Kinaya Dewi; Maharani Ikaningtyas (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Technological changes are rapidly changing industry competition. Companies need to take steps so that employees can adapt to changes and acquire skills that are in line with technological and market developments. Quality training and development is expected to increase the company's ability to face future challenges. This study combines a qualitative approach with a descriptive methodology. This approach was chosen because it has a descriptive and exploratory nature that has the aim of providing an overview of the perspectives and interpretations of the research subjects. Qualitative descriptive research has a primary focus on observation and interaction. The results of this study indicate that the training and development carried out by PT IMST has been effective, PT IMST has carried out training and development according to the needs of employees. The company has implemented an evaluation system after the implementation of training and development of employees is carried out as feedback from the implementation of training and development. The conclusion that the evaluation results of training and development have a positive impact on employees and a high level of employee participation, so that the implementation is effective based on its measurements.